Rapid and sensitive quantification of intracellular glycyl-sarcosine for semi-high-throughput screening for inhibitors of PEPT-1 - Linde, Teresa von; Bajraktari-Sylejmani, Gzona; Haefeli, Walter E.; Burhenne, Jürgen; Weiß, Johanna; Sauter, Max (Pharmaceutics, 2021)
The peptide transporter PEPT-1 (SLC15A1) plays a major role in nutritional supply with amino acids by mediating the intestinal influx of dipeptides and tripeptides generated during food digestion. Its role in the uptake of small bioactive peptides and various therapeutics makes it an important target for the investigation of the systemic absorption of small peptide-like active compounds and prodrug strategies of poorly absorbed therapeutics. The dipeptide glycyl-sarcosine (Gly-Sar), which comprises an N-methylated peptide bond that increases stability against enzymatic degradation, is widely utilized for studying PEPT-1-mediated transport. To support experiments on PEPT-1 inhibitor screening to identify potential substrates, we developed a highly sensitive Gly-Sar quantification assay for Caco-2 cell lysates with a dynamic range of 0.1 to 1000 ng/mL (lower limit of quantification 0.68 nM) in 50 µL of cell lysate. The assay was validated following the applicable recommendations for bioanalytic method validation of the FDA and EMA. Sample preparation and quantification were established in 96-well cell culture plates that were also used for the cellular uptake studies, resulting in a rapid and robust screening assay for PEPT-1 inhibitors. This sample preparation principle, combined with the high sensitivity of the UPLC-MS/MS quantification, is suitable for screening assays for PEPT-1 inhibitors and substrates in high-throughput formats and holds the potential for automation. Applicability was demonstrated by IC50 determinations of the known PEPT-1 inhibitor losartan, the known substrates glycyl-proline (Gly-Pro), and valaciclovir, the prodrug of aciclovir, which itself is no substrate of PEPT-1 and consequently showed no inhibition in our assay.
Gesehen am 09.09.2021